2016
DOI: 10.1111/apm.12571
|View full text |Cite
|
Sign up to set email alerts
|

HuR in pheochromocytomas and paragangliomas – overexpression in verified malignant tumors

Abstract: Pheochromocytomas and paragangliomas are rare, neural crest-originating, neuroendocrine tumors. HuR is an mRNA-binding protein of the ELAV/Hu-protein family, which participates in posttranscriptional regulation of many cancer-associated genes. HuR expression has been connected with aggressive behavior of several malignancies. Cyclooxygenase-2 (COX-2) is also expressed in several malignant tumors, and its expression is regulated by HuR. Tissue microarray of 153 primary pheochromocytomas and paragangliomas was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The five mutations p.Arg161Gln, p.Gln164His, p.Val166Phe, Arg167Trp and Arg167Gln localize in a small area forming the ELAVL1 binding interface (Fig 5). Increased expression of this protein was recently proposed [68] to be linked with the metastatic potential of both paraganglioma and pheochromocytoma. Similarly, the three mutations p.His115Arg, p.Trp117Gly and p.Ile151Phe localize on the androgen receptor (AR) binding interface, suggesting that these specific interactors may play a crucial role in cystadenoma insurgence (Fig 5).…”
Section: Resultsmentioning
confidence: 99%
“…The five mutations p.Arg161Gln, p.Gln164His, p.Val166Phe, Arg167Trp and Arg167Gln localize in a small area forming the ELAVL1 binding interface (Fig 5). Increased expression of this protein was recently proposed [68] to be linked with the metastatic potential of both paraganglioma and pheochromocytoma. Similarly, the three mutations p.His115Arg, p.Trp117Gly and p.Ile151Phe localize on the androgen receptor (AR) binding interface, suggesting that these specific interactors may play a crucial role in cystadenoma insurgence (Fig 5).…”
Section: Resultsmentioning
confidence: 99%
“…These in vitro study results provide an impetus for testing HuR-FNP in vivo either as a monotherapy or in combination therapy with conventional chemotherapeutics and other molecular targeted therapies for lung cancer. A study by Leijon et al [ 22 ] showed that increased expression of HuR protein is associated with metastatic potential of paragangliomas and pheochromocytomas, and cyclooxygenase 2 (COX-2) was identified as a target of HuR. In many malignancies, HuR expression is associated with high grade, poor prognosis, and large tumor size [ 23 ].…”
Section: Discussionmentioning
confidence: 99%